“Online, the counselor can't see me cry”: a systematic literature review on emotion and computer-mediated care - De Coninck, Sarah; Emmers, Elke (Frontiers in Digital Health, 2023)
Computer-mediated care is becoming increasingly popular, but little research has been done on computer-mediated care and its effects on emotion-related outcomes. The purpose of this systematic literature review is to create an overview that addresses the following research question: Is there a relationship between computer-mediated care and emotional expression, perception, emotional and (long-term) emotion outcomes? Method: This systematic literature review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and used five eligibility criteria: (1) participants: adults seeking support, (2) intervention: eHealth, (3) diagnostic criteria: transdiagnostic concept of difficulty identifying, expressing and/or regulating emotions (e.g. alexithymia) (4) comparator: either face-to-face care or no comparator (5) study design: quantitative studies or qualitative studies. Quality was assessed using the QualSyst tool.The analysis includes 25 research papers. Self-paced interventions appear to have a positive effect on emotion regulation. Interventions through videoconferencing lead to improved emotion regulation from before to after treatment, but worse emotion regulation compared to face-to-face treatment."Online, the counsellor can't see me cry": A systematic literature review on emotion and computer-mediated careThis is a provisional file, not the final typeset article Discussion: The lack of variation in the modalities studied and the emotion measurements used makes it difficult to draw responsible conclusions. Future research should examine how different modalities affect the real-time communication of emotions and how this is influenced by non-verbal cues.1